Bioaccessibility and bioactivities of phenolic compounds from roasted coffee beans during in vitro digestion and colonic fermentation. (30th August 2022) - Wu, Hanjing; Liu, Ziyao; Lu, Peiyao; Barrow, Colin; Dunshea, Frank R.; Suleria, Hafiz A.R.
Highlights: Different roasting level would not bring significant impact on the final content of phenols from coffee beans and their antioxidant potential. Proper roasting, in vitro digestion and colonic fermentation enhanced the releasement and bioaccessibility of phenolic compounds. Gastric bioaccessibility of most phenolic compounds were relatively higher. Intensive roasting substrate negatively influenced SCFAs production due to the loss of carbohydrates through thermal degradation, caramelization and Maillard reaction, Abstract: Bioaccessibility and bioactivity of phenolic compounds in coffee beans relate to roasting and digestion process. This study aimed to estimate phenolic content, antioxidant potential, bioaccessibility, and changes in short chain fatty acids (SCFAs) production during in vitro digestion and colonic fermentation of commercial roasted (light, medium and dark) coffee beans. There was no significant difference found among all three different roasting levels. TPC and DPPH were enhanced 15 mg GAE/g and 60 mg TE/g during gastrointestinal digestion, respectively. For colonic fermentation, the highest TPC and FRAP of all coffee beans was found at 2 and 4 h, respectively. The gastric bioaccessibility of most of the phenolic compounds were relatively higher due to thermal phenolic degradation. Total SCFAs production was only up to 0.02 mM because of thermal polysaccharide decomposition. Light roasted beans exhibited relatively higher phenolic bioaccessibility, antioxidant activities and SCFAs production, which would be more beneficial to gut health.